Hermeneutics of The Novel "Teruslah Bodoh Jangan Pintar" In The Perspective of The Corporate Strategy for Mineral Downstreaming Program - Riswandi, Riswandi; Furrie Lenggana , Wulan (Journal Research of Social Science, Economics, and Management, 2024)
The purpose of this study is how to interpret a writing using Jurgen Habermas' critical hermeneutic analysis, so that readers are able to trace the facts behind a manuscript, even from a fictional narrative of a novel, because there is always a meaning behind a text. This study uses qualitative methods of analytical descriptive phenomenology with secondary data. The analytical variables in this critical hermeneutics method are (1) Artifactual, that is, what is written in the novel; (2) Authentic, is facts and phenomena that occur in the real world; (3) Objectivity, namely opinions and information from experts; (4) Subjectivity, which is the opinion or thought of the researcher; (5) Existence, which is taken from Martin Heidegger's Dasein of Hermaneutic theory, is the conformity with the facts. The result of this study is that the 13 mining problems told in the narrative of the novel "Keep Being Stupid Don't Be Smart" have similarities with the reality that occurs in Indonesia. This research produces a concept of Investigative Literacy, which is a combination of literary works with journalistic products that are analyzed with critical hermeneutic methods will produce literacy skills that encourage readers to search for facts from a manuscript or story.